2009
DOI: 10.1007/s11764-009-0088-z
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to a randomized controlled trial of aerobic exercise in breast cancer survivors: the Yale exercise and survivorship study

Abstract: Future studies of exercise and breast cancer prognosis should target obese women for participation, as well as women just beginning to contemplate participation and its benefits after a cancer diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 38 publications
7
53
1
Order By: Relevance
“…The mean duration of the RCTs was 17 weeks, but the supervised exercise and/or counseling sessions associated with each intervention ranged from 3 sessions (1×/month over 12 weeks) [37] to 78 sessions (3×/week for 26 weeks) [28, 38, 40]. Most studies reported sessions that were 45 minutes or less.…”
Section: Resultsmentioning
confidence: 99%
“…The mean duration of the RCTs was 17 weeks, but the supervised exercise and/or counseling sessions associated with each intervention ranged from 3 sessions (1×/month over 12 weeks) [37] to 78 sessions (3×/week for 26 weeks) [28, 38, 40]. Most studies reported sessions that were 45 minutes or less.…”
Section: Resultsmentioning
confidence: 99%
“…In four studies [39,40,47,50], exercise adherence was defined as a percentage of the prescribed number of sessions attended (mean: 62-78%), three studies [44,46,49] used the average minutes of exercise per week (mean: 92–141 min/week), three studies [42,43,48] used the percentage of survivors meeting the exercise prescriptions (mean: 54-74%), and two studies [41,45] used the number of completed exercise sessions (mean: 3 of 12 [41] and 28 of 36 [45] sessions), see Table 2. Maintenance was defined by average minutes of PA per week (mean: 92–175) in two studies [51,55], by percentage of survivors meeting the PA guideline (mean: 37-56%) in three studies [52,53,56], and the number of survivors in the action or maintenance stage of change compared to the number of survivors in the precontemplation, contemplation or preparation stage (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have examined the cross-sectional correlates of exercise participation in breast cancer survivors, usually focusing on social cognitive variables and long term breast cancer survivors [[13]-[19]]. Moreover, several studies have examined the prospective correlates of exercise participation in breast cancer survivors [[20],[21]] or the predictors of adherence to a prescribed exercise program in long term breast cancer survivors [[22],[23]]. The determinants of exercise adherence during breast cancer chemotherapy may be quite different than during survivorship because of the known toxicities of these treatments.…”
Section: Discussionmentioning
confidence: 99%